The Relationship between Knowledge and Length of Work with the Preparedness of Health Workers Facing Flood Disasters at Community Health Centers - sari, ruri maiseptya; Dewi Aprilia Ningsih I; Anisah Tifanii (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Flood Disaster is an event or situation where an area or land is submerged due to the increasing volume of water, flood disasters often occur in Bengkulu City, so this research aims to study the relationship between knowledge and length of work with the preparedness of health workers in facing flood disasters in community health centers. This research uses an Analytical Survey approach with a cross sectional design. The population of all health workers at the Nusa Indah Community Health Center, Bengkulu City in 2023. A sample of 39 people was taken by accidental sampling. Data collection uses secondary and primary data. Data analysis using the Chi-Square test (X2) and Contingency Coefficient Test (C). The research results obtained; Of the 39 people there are 14 people who are less prepared and 25 people who are ready. Of the 39 Health Workers there are 10 Health Workers who have sufficient knowledge and 29 Health Workers whose knowledge is good. Of the 39 people there are 20 people who have worked for <10 years and 19 people >10 years, there is a relationship between knowledge and preparedness which is categorized as close, there is a relationship between length of work and the preparedness of officers in facing floods which is categorized as moderate.